Providing Additional Situational Awareness with the Use of V2X Technology to Improve the Reliability of Highly Automated Vehicles - Vorobyev, A. I.; Pletnev, M. G.; Koveshnikov, A. A.; Vorobyeva, T. V.; Morozov, D. Yu (2021 Systems of Signals Generating and Processing in the Field of on Board Communications, 2021)
The article considers an experiment on the formation of the movement of highly automated vehicles on public roads with additional situational awareness. The results of the experiment are presented on the basis of which the effectiveness of the digital model of the road and elements of the intelligent road infrastructure for ensuring road traffic safety in accordance with the "Concept for ensuring road safety with the participation of unmanned vehicles on public roads" is assessed.